The Integrasi Kajian Tafsir dan Linguistik Arab dalam Pembelajaran Bahasa Arab Kontemporer - Abd Rasyid (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to examine the integration of Qur’anic exegesis (tafsir) and Arabic linguistics in contemporary Arabic language learning and to evaluate its implications for students’ language competence and text comprehension. The research employs a qualitative approach with library research and descriptive-analytical analysis of recent scholarly literature, including international journals and Scopus-indexed articles. The findings indicate that integrating Qur’anic exegesis and Arabic linguistics enhances structural understanding of Arabic, interpretive skills in reading the Qur’anic text, and internalization of Islamic educational values. The integrative model also has implications for curriculum design, teaching strategies, and holistic evaluation methods. The study recommends implementing this model as an innovative approach in contemporary Arabic language education to strengthen both linguistic competence and character development among learners.